Low frequency (0.5Hz) rTMS over the right (non-dominant) motor cortex does not affect ipsilateral hand performance in healthy humans - Weiler,Fernanda (2008)
Reduction of excitability of the dominant primary motor cortex (M1) improves ipsilateral hand function in healthy subjects. In analogy, inhibition of non-dominant M1 should also improve ipsilateral performance. In order to investigate this hypothesis, we have used slow repetitive transcranial magnetic stimulation (rTMS) and the Purdue Pegboard test. Twenty-eight volunteers underwent 10 minutes of either 0.5Hz rTMS over right M1 or sham rTMS (coil perpendicular to scalp). The motor task was performed before, immediately after, and 20 minutes after rTMS. In both groups, motor performance improved significantly throughout the sessions. rTMS inhibition of the non-dominant M1 had no significant influence over ipsilateral or contralateral manual dexterity, even though the results were limited by unequal performance between groups at baseline. This is in contrast to an improvement in left hand function previously described following slow rTMS over left M1, and suggests a less prominent physiological transcallosal inhibition from right to left M1.